Optical Studies and Transmission Electron Microscopy of HgCdTe Quantum Well Heterostructures for Very Long Wavelength Lasers - Rumyantsev, Vladimir V.; Razova, Anna A.; Bovkun, Leonid S.; Tatarskiy, Dmitriy A.; Mikhailovskii, Vladimir Y.; Zholudev, Maksim S.; Ikonnikov, Anton V.; Uaman Svetikova, Tatyana A.; Maremyanin, Kirill V.; Utochkin, Vladimir V.; Fadeev, Mikhail A.; Remesnik, Vladimir G.; et al. (Nanomaterials (Basel, Switzerland), 2021)
HgTe/CdHgTe quantum well (QW) heterostructures have attracted a lot of interest recently due to insights they provided towards the physics of topological insulators and massless Dirac fermions. Our work focuses on HgCdTe QWs with the energy spectrum close to the graphene-like relativistic dispersion that is supposed to suppress the non-radiative Auger recombination. We combine various methods such as photoconductivity, photoluminescence and magneto-optical measurements as well as transmission electron microscopy to retrofit growth parameters in multi-QW waveguide structures, designed for long wavelengths lasing in the range of 10–22 μm. The results reveal that the attainable operating temperatures and wavelengths are strongly dependent on Cd content in the QW, since it alters the dominating recombination mechanism of the carriers.